2020
DOI: 10.1177/2284026520903214
|View full text |Cite
|
Sign up to set email alerts
|

Path to diagnosis and women’s perspectives on the impact of endometriosis pain

Abstract: Introduction: Endometriosis is a burdensome chronic disease that can be difficult to diagnose, yet few studies examine experiences along the continuum of disease state. We sought to explore women’s journeys to an endometriosis diagnosis, experience with endometriosis pain, and interactions with healthcare practitioners. Methods: An anonymous 23-question online survey was distributed to women (aged >19 years) who self-identified as having a surgical or nonsurgical diagnosis of endometriosis and living in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
(77 reference statements)
3
27
1
2
Order By: Relevance
“…This previous study also found that the treatment goals of practitioners were usually not aligned with women's own goals and needs. 37 These findings complement results from our current study, which suggest that women may not be getting sufficient information about their dyspareunia or effective treatments to mitigate their pain and lessen the negative impact painful sex has on daily lives.…”
Section: Discussionsupporting
confidence: 81%
“…This previous study also found that the treatment goals of practitioners were usually not aligned with women's own goals and needs. 37 These findings complement results from our current study, which suggest that women may not be getting sufficient information about their dyspareunia or effective treatments to mitigate their pain and lessen the negative impact painful sex has on daily lives.…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, many women experience significant delays before receiving a diagnosis of endometriosis. 11 , 29 , 30 After receiving a diagnosis, many women experience unpredictable responses to surgical and medical therapies. 31 …”
Section: Potential Life-course Impact Of Endometriosismentioning
confidence: 99%
“…Indeed, the mean age in this study was 45 years. 60 Because most women may begin feeling endometriosis-related pain during their teens, 30 the cumulative impact of endometriosis on employment and careers may be higher.…”
Section: Employment and Careermentioning
confidence: 99%
“…Data to inform about the impact of socio-economic on the access of health care were taken from Williams et al's (2010) study 'Race, Socioeconomic Status and Health: Complexities, Ongoing Challenges and Research Opportunities.' Data regarding the patient's satisfaction with care received and the impact endometriosis has on their quality of life was taken from a study exploring a patient's journey to an endometriosis diagnosis (Lamvu, et al, 2020).…”
Section: Data and Selection Of Variablesmentioning
confidence: 99%
“…Finally, these interference nodes alongside 'M: Suspected Endometriosis' are parents of 'Negative impact on Quality of Life' to determine how patients with endometriosis are affected in their day-to-day living. The information was pulled from a study exploring a patient's journey to an endometrioses diagnosis (Lamvu, et al, 2020).…”
Section: Medical Idiomsmentioning
confidence: 99%